2022
DOI: 10.11606/s1518-8787.2022056004178
|View full text |Cite
|
Sign up to set email alerts
|

Mortality inequalities measured by socioeconomic indicators in Brazil: a scoping review

Abstract: OBJECTIVE Summarize the literature on the relationship between composite socioeconomic indicators and mortality in different geographical areas of Brazil. METHODS This scoping review included articles published between January 1, 2000, and August 31, 2020, retrieved by means of a bibliographic search carried out in the Medline, Scopus, Web of Science, and Lilacs databases. Studies reporting on the association between composite socioeconomic indicators and all-cause, or specific cause of death in any age group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(135 reference statements)
0
3
0
1
Order By: Relevance
“…Other study on leading causes of death in Brazil observed that between 2000 and 2012 the mortality rates due to cerebrovascular diseases, hypertensive diseases and circulatory system diseases were influenced by socioeconomic factors. There was a significant inverse association between socioeconomic factors and mortality rates 32 . In view of this, it is possible that improvement in socioeconomic conditions of these localities, as evidenced by increasing sociodemographic indices 33 over the period, influenced the high percentage reduction in childhood stroke mortality; however, at the same time, inefficient or inadequate data recording may have favored underreported deaths.…”
Section: Discussionmentioning
confidence: 90%
“…Other study on leading causes of death in Brazil observed that between 2000 and 2012 the mortality rates due to cerebrovascular diseases, hypertensive diseases and circulatory system diseases were influenced by socioeconomic factors. There was a significant inverse association between socioeconomic factors and mortality rates 32 . In view of this, it is possible that improvement in socioeconomic conditions of these localities, as evidenced by increasing sociodemographic indices 33 over the period, influenced the high percentage reduction in childhood stroke mortality; however, at the same time, inefficient or inadequate data recording may have favored underreported deaths.…”
Section: Discussionmentioning
confidence: 90%
“…Na região Nordeste existe um grande grau de desigualdade, presente no âmbito econômico e em serviços públicos como na educação e moradia. Assim, resultando em fatores gerais que facilitam a ocorrência de DIPs como o contraste social, baixa renda e baixa escolaridade, os quais influenciam na qualidade de vida e no acesso ao sistema de saúde, prejudicando assim, o tratamento e favorecendo o ciclo de autoinfecção (ICHIHARA MY, et al, 2022). Vale ressaltar que, também existem fatores condicionantes ao maior número de óbitos por DIPs entre indivíduos de determinado sexo.…”
Section: Introductionunclassified
“…In Brazil, between 1982 and 2015, IMR decreased more than 80% (from 71.3:1000 LB to 14.0:1000 LB), placing the country among those that successfully met objective number four of the Millennium Development Goals, whose target was a two-thirds reduction in the mortality of infants under 5 years old, between 1990 and 2015 [ 2 , 3 ]. The sharp decline in infant mortality in Brazil in the period was due to the expansion of access to prenatal care and hospital care for childbirth in the SUS (acronym in Portuguese for Unified Health System - Sistema Unico de Saúde), promotion of breastfeeding, increased vaccination coverage, monitoring of the child’s growth and development in the first year of life, and reduction in geographical and economic inequalities in the country, which still persist nonetheless [ 4 6 ]. In 2017, the IMR in Brazil was 13.4:1000 LB, with the South (where the Rio Grande do Sul state is located) and Southeast regions of the country showing rates below the national average (10.1 and 11.3:1000 LB, respectively), while in the North (15.4:1000 LB), Northeast (14.1:1000 LB), and Central-West region (11.7:1000 LB) the means were higher [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11].3) 7.5 (6.0-9.2) 5.0 (3.8-6.4) 4.0 (3.0-5.3) 1 6. (1.0-2.5) 1.3 (0.7-2.1) 2.9 (2.0-4.0) 2.3 (1.5-3.3) 7.7 (6.7-8.8) 5.3 (4.5-6.2) 4.1 (3.4-4.9) 2.0 (1.5-2.6) 1.4 (1.0-1.9) 3.0 (2.4-3.7) 2.2 (1.7-2.8) 3rd 36,977 9.6 (8.6-10.6) 7.4 (6.6-8.3) 5.1 (4.4-5.9) 4.1 (3.5-4.8) 1.6 (1.2-2.0) 1.3 (1.0-1.7) 2.9 (2.4-3.5) 2.0 (1.6-2.5) 8.4 (7.7-9.1) 4.9 (4.4-5.5) 4.2 (3.7-4.7) 2.2 (1.8-2.6) 1.7 (1.4-2.0) 3.2 (2.8-3.7) 2.5 (2.1-2.9) 9.9 (8.7-11.2) 8.5 (7.4-9.7) 3.9 (3.1-4.7) 3.3 (2.6-4.1) 4.9 (4.1-5.9) 4.1 (3.3-5.0) ≥ 7 108,239 5.1 (4.7-5.5) 3.4 (3.1-3.8) 2.1 (1.8-2.4) 1.5 (1.3-1.7) 1.0 (0.8-1.2) 0.6 (0.5-0.8) 1.9 (1.6-2.2) 1.3 (1.1-1.5) Type of delivery (N = 141,530) 9.4 (8.8-10.0) 6.2 (5.7-6.7) 5.6 (5.2-6.1) 1.7 (1.5-2.0) 1.4 (1.2-1.6) 3.1 (2.8-3.4) 2.5 (2.2-2.8)…”
mentioning
confidence: 99%